Shifting culture and taking action to reduce smoking and premature death among people with a mental health condition. Issue 4 (19th December 2016) - Harker, Katy; Cheeseman, Hazel
Abstract : Purpose: Mental health conditions affect almost a quarter of the population who die on average 10-20 years earlier than the general population. Smoking is the single largest cause of this gap in life expectancy. Smoking rates among people with mental health conditions have barely changed over the last 20 years during a time when rates have been steadily falling in the general population. Action is needed to address the growing difference in smoking rates among those with a mental health condition compared to the general population. The paper aims to discuss these issues. Design/methodology/approach: This work has been informed by the input of a wide range of experts and professionals from across public health, mental health and the wider NHS. Findings: People with a mental health condition are just as likely to want to stop smoking as other smokers but they face more barriers to quitting and are more likely to be dependant and therefore need more support. Quitting smoking does not exacerbate poor mental health; in fact the positive impact of smoking cessation on anxiety and depression appears to be at least as large as antidepressants. Originality/value: The full report outlines the high-level ambitions and the specific actions that must be realised to drive down smoking rates among those with a mental health condition.